Pediatric anti N-methyl-D-aspartate receptor encephalitis: a case report - Pokalkar, Apeksha; Pokalkar, Dhairyawan (International Journal of Research in Medical Sciences, 2024)
Anti-N-methyl-D-aspartate receptor encephalitis (NMDARe) is a form of autoimmune encephalitis commonly associated internal malignancy. In this report, we present the case of a 6 years girl with acute onset of left partial seizures rapidly progressed to status epilepticus. The patient had recurrent generalized convulsions requiring multiple admissions. She had dominant neuropsychiatric manifestations, polymorphic seizures, agglomeration of movement disorders and cognitive decline. She did not respond to intravenous steroids and immunoglobulins. She responded to rituximab. She was on maintained on azathioprine for eight months and stopped. Presently she is on two anti-epileptic agents and seizure free. She returned back to school with reasonably good scholastic performance. Early detection, immunomodulation and regular follow up gives good long-term outcomes.